2012
DOI: 10.1002/psp.1710
|View full text |Cite
|
Sign up to set email alerts
|

Marriage Postponement in Iran: Accounting for Socio‐economic and Cultural Change in Time and Space

Abstract: The mean age at marriage of Iranian women increased by three years between the mid‐1980s and 2000 during a period of great socio‐economic change, particularly affecting the 1971–1975 and 1976–1980 birth cohorts. This paper analyses the marriage timing and life course experience of these cohorts of women and highlights the contribution that ethnicity and changes in the socio‐economic context made to the sharp marriage delay experienced by the 1976–1980 birth cohort. A discrete time hazard model is applied to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…According to the international reports, the average age of marriage in Iran was 19 years in 1956, which has now increased to 24 years old (World Bank 2010). In addition, more than 70% of our participants experienced pregnancy within the first 5 years of marriage, which is similar to the usual delay of 4 years for pregnancy after marriage in Iran (Torabi et al 2013). These data suggest that the pattern of pregnancy has changed over time in Iran.…”
Section: Discussionsupporting
confidence: 80%
“…According to the international reports, the average age of marriage in Iran was 19 years in 1956, which has now increased to 24 years old (World Bank 2010). In addition, more than 70% of our participants experienced pregnancy within the first 5 years of marriage, which is similar to the usual delay of 4 years for pregnancy after marriage in Iran (Torabi et al 2013). These data suggest that the pattern of pregnancy has changed over time in Iran.…”
Section: Discussionsupporting
confidence: 80%
“…reported that between 1980s and 2000s, the mean age of marriage increased in Iranian women by 3 years because of socioeconomic changes. [ 17 ] This pattern has been also found in younger cohorts of women. Rahimi et al .…”
Section: Discussionsupporting
confidence: 57%
“…Changing employment patterns are not alone in reshaping marriage. Lengthening formal education is associated with changing marriage patterns in many societies (Shapiro & Gebreselassie, 2014;Torabi et al, 2013). Yet this is not available to all.…”
Section: Thematic and Conceptual Approaches To The Geographies Of Mmentioning
confidence: 99%